Pemberdayaan Ekonomi Lokal Mustahiq Berbasis Filantropi Islam Melalui Zakat Pada Lembaga Amil Zakat di Indonesia - Syarifuddin, Syarifuddin; Trimulato, Trimulato (Universitas Islam Raden Rahmat, 2024)
The purpose of research on how to empower local economies based on Islamic philanthropy through zakat at amil zakat institutions in Indonesia. The research findings show that the empowerment of the mustahiq local economy based on Islamic philanthropy through zakat amounted to Rp 3.52 trillion or 30.59% of the total distribution and its absorption capacity of 92.77% is said to be very effective in empowering the local economy of mustahiq in Indonesia. Then some local economic empowerment mustahiq based on Islamic philanthropy through zakat, namely Fair Wealth Distribution, Increasing Access and Welfare, Economic Infrastructure Development, Entrepreneurship Empowerment. Then social solidarity, shared responsibility, and economic benefits. The program contributes to the development of a more just, sustainable, and inclusive society. By managing zakat funds wisely, running programs transparently, and involving active community participation, Local economic empowerment of mustahiq through zakat can help overcome economic and social disparities and improve the welfare of Muslims as a whole.